Analisis harga saham pada PT. BTPN Syariah Tbk dengan metode EMA (exponential moving average) Tahun 2020-2022 - Wahyuni, Elina Decelita; Rafidah, Rafidah; Mubarak, Fadhlul (e-Journal Perdagangan Industri dan Moneter, 2023)
This study uses a quantitative research method that aims to apply time series charts to the shares of Bank Syariah Tbk. The right guess is the main information needed by investors in determining the next strategy in investing, one of which is the Exponential Moving Average method. This method is a time series method used to predict the future using historical data. Giving weights involves a period, so the longer the period we use, the less weighting the last value we use.With the abundance of existing data, a system that utilizes past data has been built, in other words, a time series model tries to use the past time series to predict, later the system will be useful to assist investors in predicting estimates of the magnitude of the value in the future so that they can determine the right strategy for investent.